2021
DOI: 10.1001/jamanetworkopen.2020.34553
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Text Messaging on Bowel Preparation and Appointment Attendance for Outpatient Colonoscopy

Abstract: IMPORTANCEOutpatient colonoscopy is important for colorectal cancer screening. However, nonadherence and poor bowel preparation are common. OBJECTIVE To determine if an automated text messaging intervention with a focus on informational and reminder functions could improve attendance rates and bowel preparation quality for outpatient colonoscopy. DESIGN, SETTING, AND PARTICIPANTSThis randomized clinical trial was conducted in an endoscopy center at an urban academic medical center. Adult patients scheduled for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 22 publications
2
30
0
Order By: Relevance
“…The analysis of nine studies [ 12 , 14 , 16 , 23 , 24 , 33 , 35 37 ] completed in the USA shows that supplementary education can significantly improve the rate of adequate bowel preparation for outpatients (72.1% vs 67.6%, RR:1.09, 95% CI: 1.01 to 1.19, I 2 = 65%, p = 0.03) ( S6B Fig ). A subgroup analysis based on studies in China [ 7 , 15 , 18 , 19 , 22 , 32 , 34 ] (RR:1.19, 95% CI: 1.10 to 1.28, I 2 = 78%, p <0.00001) and Spain [ 17 , 20 , 21 ] (RR:1.03, 95%CI: 1.01 to 1.06, I 2 = 0%, p = 0.007) also showed that supplementary education can significantly increase the rate of adequate bowel preparation (China: 78.7% vs 68.7% and Spain: 88.8% vs 85.8%) ( S6B Fig ).…”
Section: Subgroup Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…The analysis of nine studies [ 12 , 14 , 16 , 23 , 24 , 33 , 35 37 ] completed in the USA shows that supplementary education can significantly improve the rate of adequate bowel preparation for outpatients (72.1% vs 67.6%, RR:1.09, 95% CI: 1.01 to 1.19, I 2 = 65%, p = 0.03) ( S6B Fig ). A subgroup analysis based on studies in China [ 7 , 15 , 18 , 19 , 22 , 32 , 34 ] (RR:1.19, 95% CI: 1.10 to 1.28, I 2 = 78%, p <0.00001) and Spain [ 17 , 20 , 21 ] (RR:1.03, 95%CI: 1.01 to 1.06, I 2 = 0%, p = 0.007) also showed that supplementary education can significantly increase the rate of adequate bowel preparation (China: 78.7% vs 68.7% and Spain: 88.8% vs 85.8%) ( S6B Fig ).…”
Section: Subgroup Analysismentioning
confidence: 99%
“…The results of subgroup analysis based on different bowel preparation regimens showed that supplementary education in the 2 L PEG+ ascorbate solution (RR:1.02, 95% CI: 0.97 to 1.07, I 2 = 60%, p = 0.44) group [ 17 , 38 ] could not improve the adequate bowel preparation rate of outpatients ( S6C Fig ). However, in the split-dose 4 L PEG [ 15 , 16 , 18 , 21 23 , 32 , 35 ] (75.0% vs 68.7%, RR:1.10, 95% CI: 1.05 to 1.15, I 2 = 43%, p <0.00001) and 4 L PEG [ 7 , 19 , 33 , 37 ] (78.1% vs 64.6%, RR:1.23, 95% CI: 1.10 to 1.38, I 2 = 31%, p = 0.0004) groups, supplementary education improved the rate of adequate bowel preparation ( S6C Fig ).…”
Section: Subgroup Analysismentioning
confidence: 99%
See 3 more Smart Citations